2020
DOI: 10.1016/j.cgh.2019.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alterations in Intestinal Microbiota With Impaired Psychological Function in Patients With Inflammatory Bowel Diseases in Remission

Abstract: BACKGROUND AIMS Depression and anxiety are frequent comorbidities with inflammatory bowel diseases (IBD). Alterations to the intestinal microbiome promote not only intestinal inflammation but also psychologic function. We studied the interactions between the composition of the intestinal microbiota and psychological outcomes in patients with IBD in Switzerland. METHODS We performed a prospective study of psychological comorbidities and quality of life (QoL) in 171 participants in the Swiss IBD Cohort Study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 51 publications
7
68
0
Order By: Relevance
“…For example, the decreased level of phylum Deferribacteres found in EAP mice did decrease upon transplantation with EAP feces. Of particular interest, family Ruminococcaceae and Bacteroidaceae, and genus Lactobacillus, Turicibacter, and Bacteroides were reported to be associated with depression, 43‐45 which was consistent with the results of the present study. Although more evidence is needed to identify the specific microbiota that contributes to the development of CP/CPPS‐induced depression, the microbiota would be novel therapeutic targets for these patients.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the decreased level of phylum Deferribacteres found in EAP mice did decrease upon transplantation with EAP feces. Of particular interest, family Ruminococcaceae and Bacteroidaceae, and genus Lactobacillus, Turicibacter, and Bacteroides were reported to be associated with depression, 43‐45 which was consistent with the results of the present study. Although more evidence is needed to identify the specific microbiota that contributes to the development of CP/CPPS‐induced depression, the microbiota would be novel therapeutic targets for these patients.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the Desulfovibrionaceae family is reported in reduced proportions, 37 with a negative correlation between physiological distress and its abundance. 70 The genus Desulfovibrio degrades acidic mucin normally found in the colon. However, in CD patients, the mucus is mostly neutral, which can explain the reductions observed in these subjects.…”
Section: Dysbiosis Implicationsmentioning
confidence: 99%
“…In the current study, UC patients who accompanied by depression and anxiety are found to harbor less Prevotella_9 and Erysipelotrichaceae UCG_003, but more Sellimonas in the feces. In consistency, Prevotella, which has been found to participate in various emotion-related metabolic pathways such as tryptophan and glutamate synthesis [23], is reported to be associated with lower depression and anxiety level, psychological stress and higher quality of life in IBD patients [22]. The abundance of Prevotella is reported to be associated with hippocampus's function and structure [24].…”
Section: Discussionmentioning
confidence: 99%
“…An animal study showed that biogenic lactic acid bacterium prevented IBD-like pathology and depression-like behavior in mice via decreasing the levels of rectal and hippocampal in ammatory cytokines [21]. Currently, there is only one clinical study that has investigated the relationship between gut microbiota and mental states in IBD patients at remission stage by 16S rRNA sequencing of the feces [22], while little is known about the situations in IBD patients at active stage (which is more severe and needs more attention) and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%